2020
DOI: 10.7717/peerj.8916
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variation in the cochleae of harbour porpoises (Phocoena phocoena) and its implications for comparative studies across odontocetes

Abstract: In morphological traits, variation within species is generally considered to be lower than variation among species, although this assumption is rarely tested. This is particularly important in fields like palaeontology, where it is common to use a single individual as representative of a species due to the rarity of fossils. Here, we investigated intraspecific variation in the cochleae of harbour porpoises (Phocoena phocoena). Interspecific variation of cochlear morphology is well characterised among odontocet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…3, 4). Moreover, like Costeur et al (2018), we found no morphological similarity between Lipotes and Inia, although our sample is limited in extant representatives and might therefore be masking such characteristics, though a single specimen should be indicative of morphology (Martins et al 2020). Therefore, although numerous common adaptations are reported in the skull and postcranial skeleton of riverine dolphins (Page and Cooper 2017;Fordyce 2018;Rommel and Reynolds 2018), in agreement with Park et al (2019), we found no "river dolphin" convergent morphology for the inner ear.…”
Section: Comparisonssupporting
confidence: 49%
“…3, 4). Moreover, like Costeur et al (2018), we found no morphological similarity between Lipotes and Inia, although our sample is limited in extant representatives and might therefore be masking such characteristics, though a single specimen should be indicative of morphology (Martins et al 2020). Therefore, although numerous common adaptations are reported in the skull and postcranial skeleton of riverine dolphins (Page and Cooper 2017;Fordyce 2018;Rommel and Reynolds 2018), in agreement with Park et al (2019), we found no "river dolphin" convergent morphology for the inner ear.…”
Section: Comparisonssupporting
confidence: 49%
“…Hocking et al (2017) have suggested an alternative framework for looking at prey capture and handling, in which they treat different methods of filter‐feeding as well as grip‐and‐tear feeding as alternative methods of prey processing, versus capture, and that prey capture itself for these taxa would involve elements of raptorial or suction feeding. While we do recognize that there is overlap between the categorizations of prey capture as defined by Johnston and Berta (2011), Galatius et al (2020), and Martins et al (2020), we nonetheless find that the classification used by these latter authors to be helpful when sorting whales into different ecological categories relevant to this study.…”
Section: Methodsmentioning
confidence: 53%
“…Orbit size is a ratio of orbit length to bizygomatic width of the skull. Habitat classifications based on Jefferson et al (2008) and prey capture method based upon Johnston and Berta (2011), Galatius et al (2020), and Martins et al (2020). Numbers above box plots represent sample size of species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The periotic or the petrosal bone contains the inner ear, which is mainly divided into three parts, a cochlea, a vestibule, and semicircular canals. Active studies have been conducted thus far on the cetacean inner ear structures (e.g., Fleischer, 1976; Geisler & Luo, 1996; Luo & Marsh, 1996), and the progress of this field of research has been dramatically accelerated and become remarkable by the introduction of noninvasive computer tomography scanning (Aguirre‐Fernández, Mennecart, Sánchez‐Villagra, Sánchez, & Costeur, 2017; Churchill, Martinez‐Caceres, de Muizon, Mnieckowski, & Geisler, 2016; Costeur, 2014; Costeur et al, 2018, b; Ekdale, 2013; Gustein et al, 2014; Martins, Park, Racicot, & Cooper, 2020; Park et al, 2017, Park et al, 2017, Park et al, 2019; Racicot, Boessenecker, Darroch, & Geisler, 2019; Racicot, Darroch, & Kohno, 2018; Racicot, Gearty, Kohno, & Flynn, 2016; Thean, Kardjilov, & Asher, 2017). However, most are focused mainly on cochlear structures associated with hearing ability with relatively few studies on the vestibule or semicircular canals associated with equilibrium (Spoor, Bajpai, Hussain, Kumar, & Thewissen, 2002).…”
Section: Introductionmentioning
confidence: 99%